ANÁLISE DO PERFIL DE IDOSOS RESIDENTES EM MORADIA COLETIVA DE UMA CIDADE DA REGIÃO NOROESTE/RS - Oleiniczak, ElisÂNgela; Stumm, Eniva M. F.; Hildebrandt, Leila; Abreu, Paola B. d.; Zanetti, Tatiele G.; Kirchner, Rosane M. (Salão do Conhecimento, 2013)
Resumo